Short-circuit fault analysis and isolation strategy for matrix converters - Wang, Li-Na; De Lillo, Liliana; Brunson, C.; Empringham, Lee; Wheeler, Patrick (Central South University, 2015)
The behavior of matrix converter (MC) drive systems under the condition of MC short-circuit faults is comprehensively investigated. Two isolation strategies using semiconductors and high speed fuses (HSFs) for MC short-circuit faults are examined and their performances are compared. The behavior of MC drive systems during the fuse action time under different operating conditions is explored. The feasibility of fault-tolerant operation during the fuse action time is also studied. The basic selection laws for the HSFs and the requirements for the passive components of the MC drive system from the point view of short-circuit faults are also discussed. Simulation results are used to demonstrate the feasibility of the proposed isolation strategies.